2016
DOI: 10.1007/978-3-319-41171-2_12
|View full text |Cite
|
Sign up to set email alerts
|

Francisella Inflammasomes: Integrated Responses to a Cytosolic Stealth Bacterium

Abstract: Francisella tularensis is a facultative intracellular bacterium causing tularemia, a zoonotic disease. Francisella replicates in the macrophage cytosol and eventually triggers cytosolic immune responses. In murine macrophages, Francisella novicida and Francisella tularensis live vaccine strain lyse in the host cytosol and activate the cytosolic DNA receptor Aim2. Here, we review the mechanisms leading or contributing to Aim2 inflammasome activation, including the role of TLRs and of IFN signaling and the impli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 126 publications
0
19
1
1
Order By: Relevance
“…From these observations, we conclude that bacteriolysis is likely responsible for the release of LPS and DNA that stimulate caspase-11 and cGAS. In contrast with what we observed for R. parkeri , several facultative bacterial pathogens have evolved different mechanisms to avoid the inflammasome (Jorgensen and Miao, 2015), including modification LPS by F. novicida to avoid caspase-11 (Hagar et al, 2013; Wallet et al, 2016), downregulation of flagellin by L. monocytogenes to avoid NAIP5 (Miao et al, 2010; Shen and Higgins, 2006), and infrequent lysis by F. tularensis and L. monocytogenes to avoid AIM2 (Sauer et al, 2010; Ulland et al, 2010). We propose that inflammasome activation is a trade-off that allows for growth of a pathogen that is sensitive to IFN-I.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…From these observations, we conclude that bacteriolysis is likely responsible for the release of LPS and DNA that stimulate caspase-11 and cGAS. In contrast with what we observed for R. parkeri , several facultative bacterial pathogens have evolved different mechanisms to avoid the inflammasome (Jorgensen and Miao, 2015), including modification LPS by F. novicida to avoid caspase-11 (Hagar et al, 2013; Wallet et al, 2016), downregulation of flagellin by L. monocytogenes to avoid NAIP5 (Miao et al, 2010; Shen and Higgins, 2006), and infrequent lysis by F. tularensis and L. monocytogenes to avoid AIM2 (Sauer et al, 2010; Ulland et al, 2010). We propose that inflammasome activation is a trade-off that allows for growth of a pathogen that is sensitive to IFN-I.…”
Section: Discussioncontrasting
confidence: 84%
“…The innate immune response to microbial pathogens depends on upregulation of antimicrobial factors, secretion of cytokines, and activation of host cell death pathways (Jorgensen and Miao, 2015; Meunier and Broz, 2016; Mitchell and Isberg, 2017; Randow et al, 2013). Innate immune responses have been characterized during infection with facultative intracellular bacterial pathogens such as Listeria monocytogenes and virulent Francisella species, as well as viruses, which inhabit the host cell cytosol (Brubaker et al, 2015; McNab et al, 2015; Wallet et al, 2016). However, less well understood are the innate immune responses to obligate intracellular bacterial pathogens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considered together, the available data suggest that opsonization with natural IgG is one factor that contributes to the inability of F. novicida to cause human disease. Inasmuch as opsonization with IgG is sufficient for NADPH oxidase activation and ROS production, the ability of the absent in melanoma 2 inflammasome to curtail F. novicida growth in macrophages may be critical, and IL-1b released during macrophages pyroptosis is another factor that may contribute to prolonged neutrophil survival [32]. Thus, in the context of F. novicida infection, it is conceivable that delayed neutrophil apoptosis favors phagocytic killing of bacteria released by dying macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of isolated phagocytes and animal models demonstrate that F. novicida exhibits only some of the same virulence attributes and mechanisms as F. tularensis. In particular, F. novicida is markedly more proinflammatory, as indicated by analyses of TLR signaling, proinflammatory cytokine production, and inflammasome activation, which significantly diminish bacterial replication in macrophages and favor host defense [30][31][32]. In addition, we have shown that these organisms are opsonized by different mechanisms upon incubation in 50% normal human serum, with natural IgG binding to F. novicida eliciting neutrophil NADPH oxidase activation that does not occur following natural IgM binding to F. tularensis [16,[33][34][35][36].…”
Section: Introductionmentioning
confidence: 85%